The mTORC1 component RPTOR is required for maintenance of the foundational spermatogonial stem cell pool in mice. Issue 2 (10th September 2018) - Serra, Nicholas; Velte, Ellen K; Niedenberger, Bryan A; Kirsanov, Oleksander; Geyer, Christopher B
Abstract: The self-renewal, proliferation, and differentiation of the spermatogonial populations must be finely coordinated in the mammalian testis, as dysregulation of these processes can lead to subfertility, infertility, or the formation of tumors. There are wide gaps in our understanding of how these spermatogonial populations are formed and maintained, and our laboratory has focused on identifying the molecular and cellular pathways that direct their development. Others and we have shown, using a combination of pharmacologic inhibitors and genetic models, that activation of mTOR complex 1 (mTORC1) is important for spermatogonial differentiation in vivo. Here, we extend those studies to directly test the germ cell-autonomous requirement for mTORC1 in spermatogonial differentiation. We created germ cell conditional knockout mice for "regulatory associated protein of MTOR, complex 1" ( Rptor ), which encodes an essential component of mTORC1. While germ cell KO mice were viable and healthy, they had smaller testes than littermate controls, and no sperm were present in their cauda epididymides. We found that an initial cohort of Rptor KO spermatogonia proliferated, differentiated, and entered meiosis (which they were unable to complete). However, no self-renewing spermatogonia were formed, and thus the entire germline was lost by adulthood, resulting in Sertoli cell-only testes. These results reveal the cell autonomous requirement for RPTOR in the formation or maintenance of the foundational self-renewing spermatogonial stem cell pool in the mouse testis and underscore complex roles for mTORC1 and its constituent proteins in male germ cell development. Abstract : SSC maintenance requires RPTOR